Cost of Governance on Economic Development in Nigeria (Global Journal of Management and Business Research, 2012)
The study aims at investigating the impact of cost of governance on economic development in Nigeria. Cost of governance is captured by recurrent and capital administrative expenditures, while gross domestic product is used as a proxy for economic growth. Using data from 1970 to 2010 and the Ordinary Least Squares (OLS) technique of analysis, the study reveals that cost of governance hampers economic development in Nigeria. Therefore, there is the need to place institutional constraints on public office holders and technocrats in order to minimize the extraction of rent from the state and enhance the availability of public funds for development projects and vital sectors of the economy
Keywords: Nigeria; weak Institutions; Economic Development; Governance